2014
DOI: 10.4049/jimmunol.1401386
|View full text |Cite|
|
Sign up to set email alerts
|

Viral MHC Class I–like Molecule Allows Evasion of NK Cell Effector Responses In Vivo

Abstract: The outcome of mouse CMV (MCMV) infection varies among different inbred mouse strains depending on NK cell effector functions governed through recognition receptor triggering. NK cells from different mouse strains possess diverse repertoires of activating or inhibitory Ly49 receptors, which share some of their polymorphic MHC class I (MHC-I) ligands. By examining the NK cell response to MCMV infection in novel BALB substrains congenic for different MHC (or H-2 in mice) haplotypes, we show that recognition of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…A counterstrategy employed by viruses is the downregulation of host MHC molecules to avoid detection by T cells, but this leaves the infected cell vulnerable to lysis by natural killer (NK) cells responding to changes in MHC presentation. It is therefore plausible that CrHV2 captured an MHC homolog to disguise infected cells by using a decoy MHC molecule, a strategy that has been demonstrated for other viruses (42,43). In this context, the increased purifying selection may act to preserve the recognition of the decoy by NK cells.…”
Section: Discussionmentioning
confidence: 97%
“…A counterstrategy employed by viruses is the downregulation of host MHC molecules to avoid detection by T cells, but this leaves the infected cell vulnerable to lysis by natural killer (NK) cells responding to changes in MHC presentation. It is therefore plausible that CrHV2 captured an MHC homolog to disguise infected cells by using a decoy MHC molecule, a strategy that has been demonstrated for other viruses (42,43). In this context, the increased purifying selection may act to preserve the recognition of the decoy by NK cells.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, 264 MCMV-encoded m157 can engage Ly49 inhibitory receptors in mouse strains that do not have Ly49H 265 activation receptor-equivalents; e.g. Ly49I in 129 mice [15] and Ly49C in BALB/c [20]. We predict that 266 m157 inhibition of NK cell function will depend on whether these inhibitory receptors are in hosts with 267 appropriate MHC-I alleles for licensing.…”
Section: Deletion Of MCMV Genes M06 and M152 Prevents Nk-dependent Clmentioning
confidence: 96%
“…We predict that 266 m157 inhibition of NK cell function will depend on whether these inhibitory receptors are in hosts with 267 appropriate MHC-I alleles for licensing. Indeed, m157 effects on inhibiting NK cell control appear to be 268 MHC-dependent [20], suggesting such potential interactions. Moreover, MCMV has 11 ORFs with 269 predicted MHC-I folds [38], some of which have been verified by crystallographic studies, and thus may 270 be similarly involved in modulating NK cells.…”
Section: Deletion Of MCMV Genes M06 and M152 Prevents Nk-dependent Clmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of Ly49H+ NK cells remain as long lived cells with properties in some way analogous to memory T-cells (Box 1). Recently, it was shown that m157 variant from G1F and Smith strain MCMV can also engage inhibitory Ly49C [78,79] (d). (f) NK cells co-expressing Ly49H and C show diminished effector functions against target cells infected with G1F virus [78].…”
Section: Evasion Of Ly49 Receptorsmentioning
confidence: 99%